Development of an Initial Prototype of an Electronic-Based Government Agency Performance Accountability System (SAKIP) at State Universities with Legal Entities - Masita Nur Hayati; Yatim Riyanto; Sujarwanto; Amrozi Khamidi; Muhamad Sholeh; Karwanto (Women, Education, and Social Welfare, 2026)
Digital transformation in performance management at legal-entity state universities remains constrained by fragmented data, manual document exchange, disconnected SAKIP stages, and limited access to integrated performance information. This study aims to develop an initial prototype of an electronic Government Agency Performance Accountability System for Universitas Negeri Surabaya (UNESA), named SAKINA. Using a research and development approach, the study applied the 4D model limited to the define, design, and develop stages. Data were collected from July 2023 to June 2026 through document review, regulatory analysis, semi-structured interviews, focus group discussions, and work-process observations involving 30 purposively selected informants and 80 institutional, regulatory, and scientific documents. The define stage identified user, functional, non-functional, regulatory, and user-experience requirements. The design stage produced a three-layer architecture, module structure, role allocation, interface specifications, and integrated workflows. The develop stage generated SAKINA version 1.0 using Laravel, PostgreSQL, and Nginx. The prototype includes six module groups covering monitoring, planning, measurement, reporting, evaluation, and supporting documentation. SAKINA integrates indicators, targets, realization data, evidence, evaluation results, and follow-up actions through centralized storage, role-based access, process status, and activity logging. Further testing is required to assess usability, security, acceptance, interoperability, and implementation effects.